3D myocardial T1 mapping using saturation recovery. Issue 1 (2nd February 2017) - Nordio, Giovanna; Henningsson, Markus; Chiribiri, Amedeo; Villa, Adriana D.M.; Schneider, Torben; Botnar, René M.
Abstract : Purpose: To propose a 3D quantitative high‐resolution T 1 mapping technique, called 3D SASHA (saturation‐recovery single‐shot acquisition), which combines a saturation recovery pulse with 1D‐navigator‐based‐respiratory motion compensation to acquire the whole volume of the heart in free breathing. The sequence was tested and validated both in a T 1 phantom and in healthy subjects. Materials and Methods: The 3D SASHA method was implemented on a 1.5T scanner. A diaphragmatic navigator was used to allow free‐breathing acquisition and the images were acquired with a resolution of 1.4 × 1.4 × 8 mm 3 . For assessment of accuracy and precision the sequence was compared with the reference gold‐standard inversion‐recovery spin echo (IRSE) pulse sequence in a T 1 phantom, while for the in vivo studies (10 healthy volunteers) 3D SASHA was compared with the clinically used 2D MOLLI (3‐3‐5) and 2D SASHA protocols. Results: There was good agreement between the T 1 values measured in a T 1 phantom with 3D SASHA and the reference IRSE pulse sequences (1111.6 ± 31 msec vs. 1123.6 ± 8 msec, P  = 0.9947). Mean and standard deviation of the myocardial T 1 values in healthy subjects measured with 2D MOLLI, 2D SASHA, and 3D SASHA sequences were 881 ± 40 msec, 1181.3 ± 32 msec, and 1153.6 ± 28 msec respectively. Conclusion: The proposed 3D SASHA sequence allows for high‐resolution free‐breathing whole‐heart T 1 ‐mapping with T 1 values in good agreement with the 2D SASHA and improved precision. Level of Evidence: 2 Technical Efficacy: Stage 1 J. MAGN. RESON. IMAGING 2017;46:218–227